Clinical study of Pfaffia glomerata (Spreng.) Pedersen on healthy middle-aged and elderly men: assessment of the effects on cognition (Revista Brasileira de Plantas Medicinais, 2024)
Pfaffia glomerata (Spreng.) Pedersen (PG) has potential effects on cognitive function, yet it has not been studied in humans. This randomized, double-blinded, placebo-controlled study investigated the effect of PG roots standardized extract (1.0% of β-ecdysone) on cognition in healthy middle-aged and elderly men. Thirty-eight men (aged 50-73) were randomized into Placebo and PG groups and later reorganized into Placebo and PG athlete and non-athlete subgroups; each subject took one capsule of PG extract (300 mg) or brown sugar as placebo (500 mg) twice daily for 6 months. Cognitive function was assessed at baseline and at in the 6th-month using neuropsychological tests. The PG extract was well tolerated, with only one dropout case in the placebo group. Overall, there were no significant differences between the groups from initial to final evaluation. However, subgroup analysis by physical activity profile showed significant improvements in WMS-digit span forward (Athletes’ PG group) and WMS-logical memory (Athletes and Non-athletes’ PG groups); conversely, negative interference was found in Toulouse-Pierón Q and WMS-orientation subtests on Non-athletes’ PG group.  These findings suggest that PG extract has both negative and positive effects on cognition in healthy middle-aged and elderly men. But more research is needed to better understand its effects.